Determination of antibiotic resistance of Salmonella isolated from pork, beef, and chicken meat at the retail markets in Hanoi - Viet, Nguyen Thanh; Minh, Nghiem Ngoc; Bich Thuy, Vo Thi (Vietnam Journal of Biotechnology, 2018)
Salmonella resistance to antimicrobials is a major health problem in the world. Thus, we conducted a cross-sectional study to determine the prevalence of Salmonella serovars isolates from retail meats in Ha Noi and their susceptibility to 8 antimicrobials commonly used in the treatment and growth promotion in domestic livestocks in Vietnam. Salmonella was detected in 25/90 (27.8%) samples. Nine different serovars were identified, including S. Typhimurium (44%), S. Derby (16%), S. Warragul, S. Indiana, S. Rissen (8%), and S. London, Meleagridis, Give, Assine (4%). S. Typhimurium (44 %) is the most prevalent types. Resistance to at least one antibiotic was showed in 13 strains (52%). All isolates were 44% (11/25) resistant to streptomycin and tetracycline, 32% (8/25) resistant to chloramphenicol. The multiple antimicrobial resistance accounted for 69.2% of isolates (9/13). All strains were susceptible to ceftazidime. This data indicated that the retail meats could constitute a source of human exposure to multidrug-resistant Salmonella and therefore could be considered a potential vehicle of resistant Salmonella foodborne diseases. There is an urgent need for surveillance and control programmes on Salmonella and use of antimicrobials in Vietnam to protect the health of consumers.